2007
DOI: 10.1148/radiol.2431060477
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hypertension: Noninvasive Detection with Phase-Contrast MR Imaging

Abstract: The average blood velocity throughout the cardiac cycle is strongly correlated with pulmonary pressures and resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
3
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(173 citation statements)
references
References 39 publications
6
160
3
4
Order By: Relevance
“…several studies have shown the potential use of a variety of phase-contrast MR imaging-derived parameters in the evaluation of pulmonary hypertension ( 28,29 ). A combined MR protocol, which might include pulmonary fl ow information derived from phasecontrast imaging in addition to perfusion and angiographic information provided by contrast-enhanced techniques, may be helpful for assessing the global pulmonary circulation status in patients with different types of pulmonary hypertension.…”
Section: Referencesmentioning
confidence: 99%
“…several studies have shown the potential use of a variety of phase-contrast MR imaging-derived parameters in the evaluation of pulmonary hypertension ( 28,29 ). A combined MR protocol, which might include pulmonary fl ow information derived from phasecontrast imaging in addition to perfusion and angiographic information provided by contrast-enhanced techniques, may be helpful for assessing the global pulmonary circulation status in patients with different types of pulmonary hypertension.…”
Section: Referencesmentioning
confidence: 99%
“…Investigators in a 2007 study 15 examined 59 PH patients who underwent both right-sided heart catheterization and phase-contrast MRI. The average PA velocity had the best correlation with mean PA pressure, systolic PA pressure, and PVR index.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Stroke volume (SV), a useful measure for PAH, can be calculated with pulmonary arterial ‰ow. Long-term follow-up suggests that a 10-mL change in SV is clinically important in patients with PAH.…”
Section: Evaluation Of Pulmonary Circulation Using Phase-contrast Cinmentioning
confidence: 99%
“…17 Several parameters, including acceleration time, acceleration volume, ratio, and average velocity, have been proposed for quantitative analysis of the time-velocity curve. 16 Sanz and colleagues 16 assessed the diagnostic value of these parameters in PAH in 59 subjects and found that average velocity correlated best with mPAP. PAH was correctly diagnosed with average velocity above the cutoŠ value of 11.7 cm/s (measured in expiration), with sensitivity of 92.9z (39/42) and speciˆcity of 82.4z (14/17).…”
Section: Evaluation Of Pulmonary Circulation Using Phase-contrast Cinmentioning
confidence: 99%
See 1 more Smart Citation